Efeito da aplicação imediata e tardia de diferentes sistemas de acabamento/polimento sobre a rugosidade de superfície, microdureza e microinfiltração de uma resina composta à base de silorano - Fernanda Carvalho de Rezende (2013)
The proper finishing and polishing of composite restorations are important steps in restorative dentistry, favoring aesthetics, periodontal tissue health and longevity of restorations. The hypothesis tested in this study was the similarity between the systems of finishing/polishing and the time of its application on surface roughness, hardness and microleakage of a resin low shrinkage based silorane. The factors studied in this experiment in vitro systems were finishing/polishing in four levels: control (polyester strip), Sof - lex® (3M ESPE), Astropol kit® (Ivoclar Vivadent) and Enhance System® (Dentsply), and the time of its application on two levels (immediate and delayed). The experimental units were made following a randomized complete block design. The dependent variables were: a measure of surface roughness average (Ra-m), determined in rugosimeter (n=20), the Vickers hardness measured on microhardness (n=10), and microleakage in dentin and enamel margins, measured by scores penetration of dye (n=10). The effect of the type of finishing and polishing, the time of their application and their interactions on the surface roughness and hardness was investigated by ANOVA and post-hoc Scheffé. The median microleakage scores were compared using the Kruskal-Wallis test, the enamel and dentin substrates. Comparison of the levels of factor type polishing was performed using the Mann-Whitney test. The results of all tests were considered significant at the 5% level. ANOVA showed a significant effect of type of polishing (p<0.0001) on the surface roughness. There was no significant effect of the factor time of application of polishing (p=0.2851) or the interaction time of application X type of polishing. There was a significant effect of type of polishing (p<0.0001) and factor block (p<0.0001) on the hardness, but there was no significant effect of time of application of polishing (p=0.500) nor the interaction of time X application type polishing (p=0.313). For the enamel substrate, there was no significant effect of type of polishing on microleakage (p=0.300), but statistically significant difference was observed for the time of application, with the highest scores were observed in the group subjected to the polishing stage (p=0.009). In dentinal margins, type of polishing significantly influence the microleakage (p=0.033), but there was no significant effect of time of application of polishing (p=0.313). The data presented show that the immediate polishing did not influence the surface roughness and microhardness of a composite microleakage low shrinkage based silorane. Considering the three properties studied, the null hypothesis was partially accepted since the time of application of polishing showed no effect on the roughness, hardness and microleakage, however, no system of finishing and polishing can be preferentially recommended for not having shown superior performance to other.